Application of NFT-based aquaponics technology to optimize fish production in Yogyakarta, Indonesia - Risky Setiawan; Dheny Wiratmoko; Tri Wulaningrum; Nurul Huda; Syahri Ramadan; Kris Setyaningsih (Journal of Community Service and Empowerment, 2025)
The soil condition in Iroyudan Hamlet, in limestone soil, is one of the obstacles for agriculture, so it is necessary to introduce new methods. This community service activity aims to train the Golden Valley of Iroyudan Hamlet's people to utilize agricultural land to cultivate catfish and kale vegetables. The aquaponics-based NFT (Nutrient Film Technique) is a method that is suitable for use on agricultural land, especially in dry land areas. This program is carried out by providing training in making aquaponic prototypes with a focus on cultivation on catfish and kale vegetables. The target in this training activity is a group of women farmers who already have experience and skills in managing agriculture. The success of this service activity is shown by the improvement of the understanding and skills of the trainees in using acuponic prototype media. The results of aquaponic design that have been developed through the medium of combining paralon pipe materials and steel with a hinge system make it easier to carry out the catfish harvesting process. Meanwhile, the kale harvest, which originally only used one paralon, became three paralons with an increase in yield from 10 kg to 25 kg per month.